Towards tellurium-free thermoelectric modules for power generation from low-grade heat - Ying, Pingjun; He, Ran; Mao, Jun; Zhang, Qihao; Reith, Heiko; Sui, Jiehe; Ren, Zhifeng; Nielsch, Kornelius; Schierning, Gabi (Nature Communications, 2021)
Thermoelectric technology converts heat into electricity directly and is a promising source of clean electricity. Commercial thermoelectric modules have relied on Bi2Te3-based compounds because of their unparalleled thermoelectric properties at temperatures associated with low-grade heat (<550 K). However, the scarcity of elemental Te greatly limits the applicability of such modules. Here we report the performance of thermoelectric modules assembled from Bi2Te3-substitute compounds, including p-type MgAgSb and n-type Mg3(Sb,Bi)2, by using a simple, versatile, and thus scalable processing routine. For a temperature difference of 250 K, whereas a single-stage module displayed a conversion efficiency of 6.5%, a module using segmented n-type legs displayed a record efficiency of 7.0% that is comparable to the state-of-the-art Bi2Te3-based thermoelectric modules. Our work demonstrates the feasibility and scalability of high-performance thermoelectric modules based on sustainable elements for recovering low-grade heat.
CRIS-Team Scopus Importer:2022-04-14